AKSES USAHA MIKRO KECIL DAN MENENGAH KE PERBANKAN DI KABUPATEN GUNUNG KIDUL DAN SLEMAN - Gidion P. Adirinekso (Jurnal Riset Manajemen dan Bisnis, 2011)
Many survei and research found that Micro, small and medium entreprizes, have some difficulties to access banking sector for a credit. Many constraints to the banking sector can be devided into two categories, first is financial factors and the other is non financial factors.Using logistic regression with 200 respondents, this paper want to identify key factors to access the bank. It found that financial factors did not cause their probability to acces the bank increasingly. But, non financial factor, that is their experiences to have relation withtheir supplier, was caused their probability to access bank sector significantly. From this result, the policy and framework to support Micro, small and medium entreprizes accessingthe banking sectors should consider their relationships with their supplier, or more wider their communication and skill to make sustainable network.Keywords: Access to Banking, SMEs, Credit